Efficient synthesis of N-doped porous carbon nanoribbon composites with selective microwave absorption performance in common wavebands. (30th April 2021) - Wang, Jiqi; Wu, Fei; Cui, Yuhong; Zhang, Aibo; Zhang, Qiuyu; Zhang, Baoliang
Abstract: One-dimensional carbon-based nanomaterials possess unique advantages in the field of microwave absorption due to their special structure. Structure design and synthesis method development of new one-dimensional carbon-based microwave absorbers are of great significance. In this paper, a rapid preparation method for N-doped porous carbon nanoribbon composites is reported, and a series of high-efficiency lightweight microwave absorbers have been obtained. They can meet the requirements of different microwave absorption scenarios. Firstly, an organic-inorganic hybrid nanomaterial with ribbon-shaped structure (HNR) is synthesized by solvothermal system. Then, N-doped porous carbon nanoribbon composites with different components are obtained by using HNR as precursor and being calcined at different temperature. The microwave absorbing properties show frequency selectivity. ZnS/ZnO@N-doped porous carbon nanoribbons (ZnS/ZnO@NPCNRs) exhibit best absorption performance in Ku band and achieve full band absorption with a minimum reflection loss of −56.1 dB. ZnS@N-doped porous carbon nanoribbons (ZnS@NPCNRs) have the strongest absorption in X band. The minimum reflection loss is −55.3 dB. N-doped porous carbon nanoribbons (NPCNRs) show obvious advantages in C band and S band under an ultra-low filler content of 4%. This work proposes a rapid synthesis method for ribbon-shaped carbon-based nanomaterials and provides new candidates for different microwave absorption scenarios. Graphical abstract: Image 1